دراسة مقارنة سريرية وشعاعية لرفع الجيب الفكي بتقنية البالون عند وجود أسنان مجاورة لمنطقة الفقد مقابل غياب أسنان مجاورة لمنطقة الفقد - المدلل, ياسر; الياس, جول (Latakia University Journal -Medical Sciences Series, 2013)
يبدأ الجيب الفكي بالهبوط عند قلع الأسنان العلوية الخلفية مما يستدعي إجراء رفع لقاع الجيب الفكي عند التخطيط لزرع الأسنان في هذه المنطقة ومن أكثر الاختلاطات حدوثا عند رفع الجيب هو انثقاب الغشاء المبطن للجيب الفكي، إذ تتراوح نسبة حدوثه بين 5,5 – 56.16 % . تعتبر طريقة البالون آمنة وفعالة وهي تستطب بشكل خاص في حالات الفقد السني العلوي الخلفي الصغير (1-2 ) سن. يعتمد مبدأ هذه الطريقة على ضخ سائل ( السالين عادة ) ضمن البالون مما يؤدي لرفع قاع الجيب الفكي بشكل مستمر وبطيء. هَدَف البحث إلى تقييم الزيادة في ارتفاع العظم عند رفع الجيب الفكي بطريقة البالون عند وجود أسنان مجاورة لمنطقة الفقد ومقدار الزيادة في ارتفاع العظم عند عدم وجود أسنان مجاورة لمنطقة الفقد . تم في هذا البحث تطبيق تقنية البالون في رفع الجيب الفكي على 30 حالة رفع جيب فكي عند 27مريضاً لديهم درد علوي خلفي وبحاجة لإجراء عملية رفع جيب فكي من أجل الزرع . تم تقسيم المرضى لمجموعتين الأولى ضمت 15 حالة رفع جيب بالبالون مع وجود أسنان مجاورة والثانية ضمت 15 حالة رفع جيب بالبالون بدون وجود أسنان مجاورة. تتم متابعة المرضى في 5 فترات زمنية بعد العمل الجراحي بالصور الشعاعية بطريقة التصوير السني المخروطي CBCT (بعد العمل مباشرة ,بعد 3 شهور, بعد 6 أشهر, بعد 9 أشهر ,بعد سنة واحدة ) . استنتج البحث أنه عند مستوى الثقة R = 95% لا توجد فروق دالة إحصائيا في مقدار الزيادة في ارتفاع العظم عند وجود أسنان مجاورة لمنطقة الفقد وعدم وجود أسنان مجاورة لمنطقة الفقد . أوصى البحث باستخدام طريقة رفع قاع الجيب الفكي بالبالون عند وجود أسنان مجاورة لمنطقة الفقد وعدم وجود أسنان مجاورة لمنطقة الفقد. The floor of maxillary sinus starts to get down when the posterior upper teeth are extractedو which demand proceed sinus floor elevation when we plan to put dental implant in this place. The most common complication that happens in this procedure is membrane perforation which took place at range of 5,5- 56.16 %. So the method of sinus lifting with balloon has spread which is considered a safe and affective method and it is indicated especially when there is a small dental loss (1-2 teeth ). The principle of this method depends on pumping a liquid ( saline usually ) into the balloon which causes sinus floor elevating slowly and continuously. The research aims to evaluate bone thickness when sinus floor elevated with balloon when there are adjacent teeth and when there are not. The balloon technique of sinus floor lifting is applied on 30 sinus lifting cases in 27 patients who have more than 2 teeth dental loss in posterior superior area and need sinus lifting for dental implantation in this area. The patients were divided into two groups: the first one included 15 cases of sinus floor lifting with balloon and there are approximate teeth to the edentulous area. The second group included 15 cases of sinus floor lifting with balloon when there are no adjacent teeth. Patients had been followed up in 5 periods using dental cone beam radiography ( after the surgery, after 3 months, after 6 months, after 9 months, after 1 year ). The research showed in the two groups that At confidence level of R = 95 % there were no statistic variations of the range of success, when there are adjacent teeth to the edentulous area and when there are not. The research recommends using balloon technique of sinus floor lifting when there are adjacent teeth and when there are not .